1992
DOI: 10.1002/j.1460-2075.1992.tb05186.x
|View full text |Cite
|
Sign up to set email alerts
|

RXR alpha, a promiscuous partner of retinoic acid and thyroid hormone receptors.

Abstract: Retinoic acid receptor (RAR), thyroid hormone receptor (T3R) and vitamin D3 receptor (VD3R) differ from steroid hormone receptors in that they bind and transactivate through responsive elements organized as direct rather than inverted repeats. We now show that recombinant RAR and T3R are monomers in solution and cannot form stable homodimeric complexes on their responsive elements. Stable binding of the receptors to their responsive elements requires heterodimerization with a nuclear factor. This auxiliary fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
231
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(243 citation statements)
references
References 47 publications
12
231
0
Order By: Relevance
“…Recently it has been shown that both PML-RARa and PLZF-RARa silence the transcription of RA responsive genes under physiological concentrations of RA (Grignani et al, 1998;He et al, 1998;Lin et al, 1998). In light of these studies, as well as the fact that RAR/RXR heterodimerization is required for RAR function Bugge et al, 1992;Zhang et al, 1992), it is surprising that PML-RARa/RXRa heterodimers do not appear essential for PML-RARa's e ect on di erentiation (Grignani et al, 1996). Taken together, however, it appears that PML-RARa, PLZF-RARa, and possibly NPM-RARa disrupt wildtype RARa function by sequestering RXRa to co-repressor complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been shown that both PML-RARa and PLZF-RARa silence the transcription of RA responsive genes under physiological concentrations of RA (Grignani et al, 1998;He et al, 1998;Lin et al, 1998). In light of these studies, as well as the fact that RAR/RXR heterodimerization is required for RAR function Bugge et al, 1992;Zhang et al, 1992), it is surprising that PML-RARa/RXRa heterodimers do not appear essential for PML-RARa's e ect on di erentiation (Grignani et al, 1996). Taken together, however, it appears that PML-RARa, PLZF-RARa, and possibly NPM-RARa disrupt wildtype RARa function by sequestering RXRa to co-repressor complexes.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that in parental P19 EC cells none of these elements are occupied before RA treatment, but occupancy is induced at these elements after RA treatment without requiring new protein synthesis (except for the Inr which exhibits delayed occupancy). Thus, even though unliganded RXR/RAR heterodimers bind to the RARE in vitro (Yu et al 1991;Leid et al 1992;Marks et al 1992;Bugge et al 1992;Kliewer et al 1992), RARE occupancy in this promoter in vivo is ligand dependent (as defined within the constraint of the genomic footprinting method employed here, see the summary figure). Figures 5A and 5B show the results of genomic footprinting analysis performed for a control and 1 C2 clone before and after RA treatment.…”
Section: C2 Inhibits Rar 2 Promoter Occupancy In Vivomentioning
confidence: 98%
“…Genes in this family are activated by small molecule hydrophobic ligands and form homodimers and heterodimers that then interact with specific response elements in regulatory regions of target genes (Applebury et al, 2000;Bugge et al, 1992). This family includes genes encoding the retinoid receptors (RARs and RXRs), thyroid hormone receptors (TRs), and a number of "orphan" receptors for which ligands have not been identified.…”
Section: Nuclear Hormonementioning
confidence: 99%